The Humour of Homer and Other Essays - Butler, Samuel, 1835-1902; Jones, Henry Festing, 1851-1928; Streatfeild, R. A. (Richard Alexander), 1866-1919 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Humour of Homer and Other Essays" by Samuel Butler is a collection of essays written in the late 19th century that explores themes related to literature, art, and science, with a particular focus on humor in classical works. The book contains a significant essay titled "The Humour of Homer," which discusses the comedic aspects of Homer's epics, particularly the Iliad and the Odyssey, while also questioning the traditional interpretations and authorship of these texts. The essays reflect Butler's unique perspective as a critic and a thinker of his time, aiming to shed light on the nature of creativity and the human experience through the lens of humor. The opening of the collection presents an introduction by R. A. Streatfeild that discusses Butler's intentions in his essays and their historical context, providing a biographical backdrop for his analysis of Homer. Butler begins his exploration of Homer's works by emphasizing the importance of understanding the poet not only as a revered figure but as a relatable, flawed human being. He delves into the characters of the Iliad, particularly focusing on Achilles' relationship with the gods and his mother, Thetis, while highlighting the humor and wit in their interactions. This sets the stage for a broader discussion about the nature of humanity as mirrored in ancient texts, questioning traditional interpretations and inviting readers to adopt a more nuanced view of both Homer and the themes within his works. (This is an automatically generated summary.)
Sketch of the life of Samuel Butler, author of Erewhon -- The humour of Homer -- Quis desiderio...? -- Ramblings in Cheapside -- The aunt, the nieces, and the dog -- How to make the best of life -- The sanctuary of Montrigone -- A medieval girl school -- Art in the valley of Saas -- Thought and language -- The deadlock in Darwinism: part I -- The deadlock in Darwinism: part II -- The deadlock in Darwinism: part III.
Release date is 2004-06-01
Transcribed by David Price
Keywords: Essays; Homer -- Humor; Greek wit and humor -- History and criticism